O brega cibermórfico de Wanderley Andrade: pontos de inflexão no mercado musical contemporâneo - SAGICA, Frank de Lima. (Universidade Federal do Pará, 2024)
This thesis proposes to investigate how the production, circulation and consumption of music developed during and after facing the pandemic caused by the SARS-CoV-2 virus, having as an ethnographic cut the singer Wanderley Andrade, approaching his production with an interpretative look , its adaptability and its articulations on the main digital platforms, which were profitable tools for the artist to maintain himself in the period of social isolation imposed as a way of containing the contagion and proliferation of COVID-19. I propose to focus on the point of inflection that demarcated the significant changes in the marketing and positional meaning of digital stops in the years 2020/2021 , focusing on the emergence and application of emergency public notices and cultural festivals created by the Government of the State of Pará, which were: Lei Aldir Blanc, Te Quieta em Casa and Minha Banda na Cultura . For this, an interview was conducted with the music artist, composer, researcher, music producer and director of the music department of the State Secretariat of Culture of Pará (SECULT) – Allan Carvalho. All of these measures were essential for the survival of many professionals, including not only artists, but also other music professionals, such as roadies, illuminators, sound technicians, DJs, among others. Through the transformations promoted by technological advances, this thesis proposed a new conceptual-analytical model, defined by me as neopersona cybermorphic , used for a better theoretical framework on the phenomenon of the new identity profile that transits in cyberspace, which has affective individuality , virtual nomadism and identity metamorphosis , particularities that support the construction of a mentality that constantly metamorphoses, as a result of technological advances in constant flux, a representative pattern of contemporary societies. It can be inferred that brega, in addition to its grounded conception as a rhythm, also comprises a series of conflicts, social and power relations; opposition to the dominant classes; of adaptations that were made in contrast to the new musical trends that emerged throughout history. In this sense, Wanderley Andrade is the perfect stereotype of this cybermorphic mutation, evidenced throughout his journey as a tacky artist, whether in the eclecticism of his musical repertoire, in his peculiar clothing or in the fusion of local and global aesthetics. This intellectual proposition also intends to launch material that can serve as a bibliographic base for future research that may relate to aspects related to a supposed cybernetic post-modernity. Virtual ethnography was used as a methodological tool, given the difficulty in collecting data in person, as a result of the isolation measures of the pandemic period. The use of new technologies and media, the adaptability of the music market, as well as the analysis of the everyday particularities of a society in transition are themes dear to this study, with ethnomusicology as an elementary key to elucidate the intermedium in which confluences and disruptions occur , among which: music market, glocalization , tribalism, tradition and technology, themes that can , consequently, bring contributions not only to the theoretical field but also to the cultural scope.